Dismissal of an Advocate/Procurator: Canon 1486 - Mendonça, Augustine (CLSA advisory opinions, 2001-2005, 2001)
The advocate/procurator was dismissed by the petitioner, who wrote a letter to the first instance judicial vicar revoking the mandate of appointment for the advocate/procurator he had appointed because he felt that the advocate/procurator did not give appropriate pastoral consideration to his situation. The advocate/procurator was appointed for both instances. The petitioner gave a new mandate to another advocate/procurator who accepted it and signed it. Copies of this new mandate were sent to the appeal tribunal and to the first advocate/procurator. Is this action of removal of an advocate/procurator by the petitioner legitimate? What is the role of the judge in this type of a situation?